2012
DOI: 10.3109/14767058.2011.648242
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies and their obstetric outcome in two selected age groups of teenage women in Greece

Abstract: Early teenage pregnancies have always been considered of increased risk for obstetric complications. Prevention of adolescent pregnancy, by wide use of effective contraception programs, would decrease its frequency and intensive care of pregnant adolescents may reduce the pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Similarly, Tsikouras et al have reported that early period adolescent pregnancy is an important risk factor for birth before the 32nd gestational week. 1 Van Winter et al reported a decreased rate of preterm birth with every passing year after the menarche together with the increasing GA. 24 This could be due to (1) inadequate maternal nutrition, 25 (2) the lack of adequate maturation of the hypothalamohypophyseal axis for the maintenance of the pregnancy, 13 (3) the lack of adequate uterine and cervical maturation, 26,27 (4) the high rate of genitourinary tract infection in the early period adolescent group. 28 However, it is necessary to take into account the development degree of the country and number of cases when evaluating the results.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Tsikouras et al have reported that early period adolescent pregnancy is an important risk factor for birth before the 32nd gestational week. 1 Van Winter et al reported a decreased rate of preterm birth with every passing year after the menarche together with the increasing GA. 24 This could be due to (1) inadequate maternal nutrition, 25 (2) the lack of adequate maturation of the hypothalamohypophyseal axis for the maintenance of the pregnancy, 13 (3) the lack of adequate uterine and cervical maturation, 26,27 (4) the high rate of genitourinary tract infection in the early period adolescent group. 28 However, it is necessary to take into account the development degree of the country and number of cases when evaluating the results.…”
Section: Discussionmentioning
confidence: 97%
“…The increased odds for both chorioamnionitis and endometritis could be due to an immature immune system of young women that makes them more susceptible to uterine infection. 11,46,47 …”
Section: Commentmentioning
confidence: 99%
“…Young adolescents also are at greater risk [30,31]. Although prospective studies that evaluate the use of risk-screening tools based on epidemiologic, demographic biomarkers and clinical indicators in routine antenatal care are still needed, there are several approaches for providing preventive care for these women.…”
Section: Section I Delivering Effective Care To Women During Pregnanmentioning
confidence: 99%